2017
DOI: 10.1371/journal.pone.0181443
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and analysis of the MADS-box gene family in bread wheat (Triticum aestivum L.)

Abstract: The MADS-box genes encode transcription factors with key roles in plant growth and development. A comprehensive analysis of the MADS-box gene family in bread wheat (Triticum aestivum) has not yet been conducted, and our understanding of their roles in stress is rather limited. Here, we report the identification and characterization of the MADS-box gene family in wheat. A total of 180 MADS-box genes classified as 32 Mα, 5 Mγ, 5 Mδ, and 138 MIKC types were identified. Evolutionary analysis of the orthologs among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 51 publications
6
53
0
Order By: Relevance
“…Of all SBP sequences with three exons, motif numbers fluctuated between 5 and 20, and the SBP-box domain had no fixed position in the sequence (Figure 2). Similar results have been seen in other species, including moss [80], moso bamboo [11], and maize [17]. At the same time, we also noticed that there were similar motifs and orders of motifs in the proteins for each group.…”
Section: Discussionsupporting
confidence: 89%
“…Of all SBP sequences with three exons, motif numbers fluctuated between 5 and 20, and the SBP-box domain had no fixed position in the sequence (Figure 2). Similar results have been seen in other species, including moss [80], moso bamboo [11], and maize [17]. At the same time, we also noticed that there were similar motifs and orders of motifs in the proteins for each group.…”
Section: Discussionsupporting
confidence: 89%
“…Y. Zhao et al, 2006;Yamada et al, 2009;Yang et al, 2017). Although overviews on MADS-box genes in wheat are available (T. Paolacci et al, 2007;Ma et al, 2017), a detailed genome-wide phylogenetic and functional characterization of wheat MIKC-type MADS-box genes is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…(2014) demonstrated the relevant role of the chloroplast DEAD-box RH3 on the growth and stress response in Arabidopsis thaliana . Interestingly, it is reported that in bread wheat the MIKC-type MADS-box TFs have key roles in plant growth (Ma et al ., 2017; Li et al ., 2018); however, even if one of these transcription factors (Traes_5AL_13E2DEC48) was a central node in the durum wheat-specific network, it was down-regulated under N starvation in comparison to the optimal N condition.…”
Section: Discussionmentioning
confidence: 99%